Democratic Republic of Timor-Leste : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Owing to poor infrastructure, limited administrative capacity, and nascent institutions, Timor-Leste is one of the most underdeveloped countries in the world. During the turmoil, two-thirds of the physical infrastructure is estimated to have been destroyed. Executive Directors stressed that fiscal policy should bear the major burden of sustaining macroeconomic stability. The authorities' decisions to address poor management and bill collection through the introduction of an external management contract and the adoption of a prepaid meter system are welcomed. The development of a medium-term fiscal strategy is also encouraged.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet